Enhancing Elderly Health Cadre Capacity Through Church-Based Community Training for Early Detection of Non-Communicable Diseases in Southwest Papua - Mustamu, Alva Cherry; Samaran, Elisabeth; Fabanyo, Rizqi Alvian (Indonesia Berdaya, 2026)
Non-communicable diseases remain a leading cause of morbidity among the elderly, particularly in underserved regions with limited access to preventive health services. This study aimed to evaluate the effectiveness of a church-based community training program in improving the capacity of elderly health cadres for early detection of non-communicable diseases in Southwest Papua. A participatory action research design with a one-group pre-test–post-test approach was applied to 17 cadres from seven congregations. The intervention consisted of interactive lectures, hands-on practice, and simulation using a structured training manual. The results showed a significant increase in knowledge scores from 54.1±12.3 to 86.5±8.7 (p